Leaf sugary disease--A physiological disorder of sorghum in North Karnataka - S.K. ANJANA DEVI, A.H. RAJASAB and (Indian Phytopathology, 2002)
Leaf sugary disease--A physiological disorder was observed on Sorghum bicolor grown during rabi season. The disease was characterized by an extensive leaf chlorosis followed by oozing of sugars. The disease was observed at flag leaf stage (2%) and it increased till harvest (72%). Steep increase in disease incidence was observed from full bloom (7%) to hard dough phases (51%). Cool, dry weather comprising low temperature (10.4 to 15.6Â°C) and low RH (20 to 43%) was prevalent during the log phase of disease development. Due to oozing of sugars, the last few leaves [11th, 12th and 13th (flag leaf)] stuck to one another, disallowing the inflorescence to emerge from the boot. Further, the affected plants attracted a variety of insects and supported an extensive bacterial and fungal colonization.